Unity of knowledge - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
The philosopher Alfred North Whitehead said, 2The fragmentation of knowledge is one of the greatest dangers facing modern civilization.3 In this edition of Matter and Beyond, we'll explore why this fragmentation poses such a threat to our deeper understanding of ourselves and the world of which we are a part.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Knowledge, Theory of